Effects of Fuel Cell Operating Conditions on Proton Exchange Membrane Durability at Open‐Circuit Voltage. Issue 2 (20th March 2020) - Zhao, N.; Chu, Y.; Xie, Z.; Eggen, K.; Girard, F.; Shi, Z.
Abstract: Proton exchange membrane fuel cells (PEMFCs) continue to face cost and durability challenges which need to be addressed before their large scale commercialization. The PEM is an essential component of the fuel cell stack and its durability is thus a critical factor for the overall fuel cell reliability. Significant membrane degradation leads to the development of internal transfer leaks and cell short circuiting irreversibly affecting the fuel cell's functionality. In this study, perfluorosulfonic acid (PFSA) membranes were investigated for the effects of operating temperature and relative humidity on membrane durability using an open circuit voltage (OCV) accelerated stress test. The response surface methodology (RSM) was used to evaluate and optimize the effects of the operating temperature and humidity. As a result, the optimum fuel cell operational region was mapped and suggested as an alternative approach to maintain membrane durability without modifying membrane materials. The mapping could provide valuable guidelines for PEMFC designers and system engineers to optimize the operating conditions during idling to achieve a targeted membrane lifetime.